Pengaruh Emotional Brand Attachment dan Brand Love Dalam Transisi dari Kepuasan Menjadi Loyalitas pada Produk Fast Fashion di Jakarta - Aprilola, Rika; Az-Zahra, Tsania Alza; Riorini, Sri Vandayuli (Peneliti.net, 2024)
This research aims to analyze the influence of Emotional Brand Attachment and Brand Love in the transition from satisfaction to loyalty to fast fashion products in Jakarta. The unit of analysis for this research is individuals who have experience shopping for fast fashion products (H&M, Uniqlo, Pull&Bear, Stradivarius, and Bershka brands) at malls in Jakarta. The data collection method used was to distribute online questionnaires with samples taken using a non-probability sampling technique with purposive sampling to respondents who had shopped for 5 types of fast fashion brands in Jakarta. Hypothesis testing is used to analyze the influence on the H&M, Uniqlo, Pull&Bear, Stradivarius, and Bershka brands. The data used in this study is primary data obtained from the results of distributing questionnaires to 119 respondents. The method of data analysis used in this study to analyze the variables owned using the instrument test method (validity and reliability test) and the goodness of fit test. In this study using SPSS and Amos software to test the hypothesis.